Analysis of clinical characteristics and genetic testing in patients with acute fatty liver of pregnancy: a retrospective study - Shi, Yixian; Wu, Haicong; Zhou, Xiaoling; Xu, Qingling; Zheng, Liqing; Li, Dongliang; Yao, Lvfeng (BMC pregnancy and childbirth, 2021)
Background Acute fatty liver of pregnancy (AFLP) is an acute, rare and potentially lethal disease typically occurring in the third trimester of pregnancy. So far, there is no effective means of prevention. Therefore, in this study, we retrospectively analyzed the clinical features of AFLP patients for a better understanding. Meanwhile, for the first time, the genetic background associated with the onset of AFLP was discussed by high-throughput sequencing, hoping to provide evidence for genetic counseling and prenatal diagnosis of AFLP. Methods Thirteen AFLP patients admitted to our hospital and other hospital from March 2012 to February 2020 were selected. Clinical data about general condition, laboratory test, liver biopsy and the prognosis of mother and fetus were collected for retrospective analysis. In addition, the peripheral blood of five patients with AFLP and one newborn infant of his mother with AFLP was sequenced with whole-exome sequencing and gene mutation was analyzed by bioinformatics methods. Results The initial symptoms of AFLP varied differently, with jaundice (9/13, 69%), fatigue (8/13, 62%) and nausea and vomiting (6/13, 46%) being the most common. Moreover, the main maternal complications were coagulopathy (13/13, 100%), followed by acute renal dysfunction (10/13, 77%). Raised serum bilirubin, transaminases and uric acid were found in all patients (100%), hypoglycemia was found in six patients (46%) and fatty liver on ultrasound was seen in five patients (5/12, 42%). One (7%) maternal death occurred and all neonates survived delivery. In addition, to our surprise, whole-exome sequencing showed that no gene mutation in related enzymes involved in fatty acid metabolism was noted in the pregnant women and children receiving genetic testing. Conclusions Early visit, early detection, early termination of pregnancy and multidisciplinary comprehensive treatment are the key factors to improve the prognosis of AFLP patients and their newborn infants. Furthermore, although limited size of study, to our knowledge, this report is the first to present the lack of common mutation involved in fatty acid oxidation in Chinese patients with AFLP via whole-exome sequencing. Thus, further studies are needed with larger and more varied samples to validate the conclusion.